EPA-enriched ethanolamine plasmalogen and EPA-enriched phosphatidylethanolamine enhance BDNF/TrkB/CREB signaling and inhibit neuronal apoptosis in vitro and in vivo. Issue 2 (11th February 2020) - Che, Hongxia; Zhang, Lingyu; Ding, Lin; Xie, Wancui; Jiang, Xiaoming; Xue, Changhu; Zhang, Tiantian; Wang, Yuming
Abstract : Our previous study showed that EPA-enriched ethanolamine plasmalogen (EPA-pPE) exerted more significant effects than EPA-enriched phosphatidylethanolamine (EPA-PE) in improving learning and memory deficit. Abstract : Our previous study showed that EPA-enriched ethanolamine plasmalogen (EPA-pPE) exerted more significant effects than EPA-enriched phosphatidylethanolamine (EPA-PE) in improving learning and memory deficit. However, the results of the mechanism study were not consistent with the improved cognitive function, which suggested that other signaling pathways might be involved. In the present study, primary cultured hippocampal neurons and cognitive deficiency rats were used to compare the effects of EPA-pPE and EPA-PE on brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase B (TrkB)/cAMP response element-binding protein (CREB) signaling and neuronal apoptosis. The in vitro experiment showed that both EPA-pPE and EPA-PE could relieve cell death and improve the cellular morphology of neurons via upregulating anti-apoptotic proteins and downregulating pro-apoptotic proteins. The in vivo experiment showed that EPA-pPE exerted more significant effects than EPA-PE in improving the number of neuronal Nissl bodies, increasing the branching of dendrites and dendritic spine density in cortical neurons, as well as improving the expression of synaptic vesicle-related proteins synaptophysin (SYN) and PSD95 via BDNF/TrkB/CREB signaling. These results indicated that EPA-pPE exerted neuroprotection at least partly through inhibiting neuronal apoptosis and enhancing the BDNF/TrkB/CREB pathway, which suggests that EPA-enriched plasmalogen can be explored as a potential therapeutic agent in long-term Alzheimer's disease therapy.